2021
DOI: 10.1590/1980-5373-mr-2021-0077
|View full text |Cite
|
Sign up to set email alerts
|

Processing of an AA7050/Al Hybrid Composites Reinforced with Multiwalled Carbon Nanotubes

Abstract: The development of carbon nanotubes reinforced metal matrix composites merits relevant attention due to its capacity of improve the hardness and strength of the metal. However, the production of this kind of composite presents many challenges, such as the dispersion and adhesion of carbon nanotubes in the metallic matrix, wich may affect the composite consolidation. The present study aimed the development of composites using an age hardening aluminum alloy reinforced with 0.5 wt.% of multiwalled carbon nanotub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Venkatesh et al [16] also observed the promising role of MoS 2 in enhancing the tribological properties of Al-TiB 2 -Graphene hybrid composite. Luana A Batista et al [17] developed hybrid composite of Al-Al7050-MWCNT by hot extrusion process and subjected to age hardening. From the results, it was clearly demonstrated that the hybrid composites have shown higher mechanical properties compared with the single phase composites.…”
Section: Introductionmentioning
confidence: 99%
“…Venkatesh et al [16] also observed the promising role of MoS 2 in enhancing the tribological properties of Al-TiB 2 -Graphene hybrid composite. Luana A Batista et al [17] developed hybrid composite of Al-Al7050-MWCNT by hot extrusion process and subjected to age hardening. From the results, it was clearly demonstrated that the hybrid composites have shown higher mechanical properties compared with the single phase composites.…”
Section: Introductionmentioning
confidence: 99%
“…Rubber nanocomposites rely heavily on the characteristics of the rubbers and fillers 1 , especially the polarity difference between those two phases. Apart from that, other factors of the filler, such as aspect ratio, degree of dispersion, and alignment; are also integral 2 . Various types of rubber nanocomposites are made from components that are dissimilar in nature.…”
Section: Introductionmentioning
confidence: 99%